Associations of employees’ identification and citizenship behavior in organization: a systematic review and a meta-analysis - Sidorenkov, Andrey V.; Borokhovski, Eugene F.; Vorontsov, Dmitry V. (Management review quarterly, 2023)
The article provides an overview of the research on the association between identifications (ID) of employees and their organizational citizenship behavior (OCB), and reports findings of a meta-analysis of empirically observed correlations (k = 149) between the two. Our analyses distinguished among six ID levels (personal, interpersonal, micro-group, group, sub-organizational, and organizational) and five OCB types identified as directed toward: individual performance, other individuals, relationships, organizational (group) performance, and maintaining rules and regulations. In addition, we systematically collected, analyzed, and reported data on geography of research, field of organization’s activity, respondents’ demographic characteristics, methods of measuring ID and OCB. In particular, we found that organizational identification is more often considered as a correlate of OCB than group and interpersonal identifications are, the cases of correlation between either sub-organizational or micro-group identifications with the OCB measures are exceedingly rare, whereas no empirical investigation of the association between personal identification and OCB could be found. The overall weighted average effect size indicates moderate positive relationships between employees’ identifications and their citizenship behaviors. Subsequent analyses of moderator variables discovered various degrees of strength of association between ID and OCB, depending on their specific combinations, so that the same level of identification could have uneven correlations with different types of OCB and vice versa. The associations between identifications and OCB strongly depend on how the latter is assessed: trough employees’ self-reports, supervisors’ evaluation, or colleagues’ assessment. Our review also addresses gaps and limitations in the existing empirical literature and discusses directions for future research.